The dilemma of petroleum rights and ownership in Malaysia: Federal vs. State - Wan Zahari, Wan Mohd Zulhafiz (2019)
This paper examines the concept of federalism in the oil and gas industry in Malaysia. Malaysia has the world’s 23rd largest crude oil reserves and 14th largest natural gas reserves. The petroleum industry is one of the 12 National Key Economic Areas (“NKEAs”) to enhance national growth under the Malaysia’s Economic Transformation Programme (“ETP”). Due to its economic significance, the petroleum industry was given priority by the Government of Malaysia. The development of the oil and gas industry in Malaysia can be divided into two stages i.e. the period before 1974 and after 1974. Prior to 1974, the ownership of hydrocarbon resources was placed under the jurisdiction of the respective 13 states forming part of Malaysia. In 1974, Petroleum Development Act (PDA) was passed by the Parliament of Malaysia. Pursuant to the PDA, a national oil company been established in the form of public listed company which is called Petroliam Nasional Berhad (PETRONAS). The national oil company was granted the entire ownership, and the exclusive rights, powers, liberties, and privileges of exploring, winning and obtaining petroleum onshore and offshore Malaysia. Each state permanently conferred its ownership, rights, powers, liberties, and privileges in the petroleum by executing the vesting instrument specified in the PDA. This paper examines the rights of ownership of the Federation and the various States of Malaysia with regards to the hydrocarbon resources at the time of the formation of the Federation of Malaysia, and the gradual changes in the ownership of the hydrocarbon resources from the States to the absolute ownership of the Federal Government in 1974. Furthermore, this paper examines the legislation regulating petroleum resources and the role of the States and Federation in the oil and gas industry prior to 1974 and after the enactment of the PDA.